Diagnosis of Victims of Bullying Behaviour Using Bayes Method - Hasugian, Abdul Halim; Furqan, Mhd.; Khairunnisa, K (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Victims of bullying behavior in the first high school students are still going on and unresolved. Victims of bullying behavior that is not easily visible to the naked eye and the lack of knowledge about bullying are problems in resolving the problem. This research is to create an expert system that can diagnose victims of bullying behavior based on the symptoms suffered by the victims of bullying to address the problems faced during this time. The Bayes method describes the relationship between the probability of A with event B has occurred. The probability of event B on the condition of event A has occurred. The occurrence of an event based on the influence gained from the observation result, Like bullying symptoms that occur in victims of bullying behavior, the Bayes method will calculate the probability and generated types of bullying experienced by students based on the knowledge that is in the can of an expert and made into an application.